The effect of iron supplementation on menstrual bleeding volume and hemoglobin level during menstrual bleeding : A randomized clinical trial - Elnaz MokhtarKalimi; Marzeyeh Loripoor; Mohsen Rezaeian; MohammadReza Gholamrezapour (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Many women around the world avoid taking iron supplements during their menstrual bleeding, thinking that menstrual bleeding will increase after taking these supplements. Due to the lack of relevant scientific evidence in this regard, this study was performed to determine the effect of iron supplementation on menstrual blood volume and hemoglobin level during menstrual bleeding. MATERIALS AND METHODS: In this three-blind randomized clinical trial, 160 non-anemic female students of Rafsanjan University of Medical Sciences were selected through a public call and then they were randomly assigned to two intervention and control groups. The intervention group was given a ferrous sulfate tablet containsing 50 mg of elemental iron daily in the first four days of bleeding for three consecutive menstrual cycles, and the control group received a placebo simultaneously. Before and after the intervention, the level of hemoglobin was measured and the Higham chart was completed in each menstrual cycle by the participants of the two groups. The obtained data were analyzed using the SPSS software version 21 and Chi-square, independent t-test, paired t-test, analysis of variance with repeated measures, and nonparametric tests. RESULTS: Before performing the intervention, the mean Higham score and hemoglobin level of the two groups were not statistically significant (P = 0.307, P = 0.670). The mean Higham score after each intervention was not statistically significant between the two groups over time or when considering the interaction of the time group (P = 0.77, P = 0.916). The hemoglobin level of these two groups did not change significantly after the intervention compared with that before the intervention (P = 0.444). CONCLUSION: Compared with a placebo, taking iron supplements containing 50 mg of elemental iron during the first four days of menstrual bleeding in non-anemic women did not change the volume of menstrual bleeding and hemoglobin level.